Kulturowo-cywilizacyjna tożsamość państwa Izrael z perspektywy rosyjskiego neokonserwatyzmu w ujęciu aleksandra G. Dugina - Składanowski, Marcin (Studia Europaea Gnesnensia, 2019)
The article aims to describe the civilizational aspect of the State of Israel in the historiosophic and geopolitical thought of Aleksandr G. Dugin, who is considered the most influential and controversial representative of modern Russian neo-conservatism. Firstly, the article presents the intellectual and political context of Dugin’s intellectual evolution. Secondly, it shows the role of the State of Israel in the conflict of civilizations. Thirdly, it describes Dugin’s interpretation of the cul-tural and civilizational identity of the State of Israel and its geopolitical conse-quences.